GE_GERICHTE P/8417/2023 vom 20. August 2024 - GE Cour de justice (2024)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;LÉSION CORPORELLE PAR NÉGLIGENCE;CONTAMINATION D'EAU POTABLE;NÉGLIGENCE;PRESCRIPTION;AMIANTE | CPP.310; CP.12; CP.125; CP.234